Using mathematics history to strengthen geometric proof skills - ÖZDEMİR, AHMET ŞÜKRÜ (ELSEVIER SCIENCE BV, 2012)
In recent years, there has been an increasing interest in integrating the history of mathematics in teaching-learning activities in the classes. The main aim of this study is to determine how such activities strengthen students' geometric proof skills and their spatial perception. This research is designed as a multiple case study. The working group is 15 students from 11th grade in a high school. Students have worked on four learning activities from the history of mathematics related the volume of solids. Then, they are answered to a questionnaire consisted of 7 open ended questions. Most of the students have accomplished geometric proofs by using dissection method. Using the smaller shapes whose volumes are easy to compute has strengthened students' geometric proof skills. Moreover, the chosen activities from the history of mathematics have attracted students' interests. To ask the volume different frusta of pyramids and prisms and to use the history of mathematics in classrooms can be considered as recommendations.
Keywords: History of mathematics; Geometric proof skills; Solid's volumes